2018
DOI: 10.1111/eci.13007
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide relieves cardiac dilated function than DPP‐4 inhibitors

Abstract: IntroductionDiabetes mellitus is a progressive disease with cardiovascular complications. This study evaluated the effects of liraglutide, a glucagon‐like peptide‐1 analogue and the dipeptidyl peptidase 4 inhibitors sitagliptin and linagliptin on cardiac function in type 2 diabetes patients with renal impairment.Materials and MethodsA total of 139 patients who were referred because of suboptimal glycaemic control were randomly assigned to liraglutide 0.9 mg/d (n = 45), sitagliptin 50 mg/d, (n = 49) or linaglip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…At baseline, the median trial mean glycated haemoglobin A1c was 8.1% and BMI was 30.1. Eligibility criteria included coronary artery disease or macrovascular disease in 35 trials, 3 6 7 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 atrial fibrillation in 1 trial, 65 heart failure in 9 trials, 66 67 68 69 70 71 72 73 74 chronic kidney disease and/or albuminuria in 37 trials, 8 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 …”
Section: Resultsmentioning
confidence: 99%
“…At baseline, the median trial mean glycated haemoglobin A1c was 8.1% and BMI was 30.1. Eligibility criteria included coronary artery disease or macrovascular disease in 35 trials, 3 6 7 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 atrial fibrillation in 1 trial, 65 heart failure in 9 trials, 66 67 68 69 70 71 72 73 74 chronic kidney disease and/or albuminuria in 37 trials, 8 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 …”
Section: Resultsmentioning
confidence: 99%
“… 22 , 23 Liraglutide and SGLT-2 inhibitors were reported to improve cardiac diastolic dysfunction. 24 , 25 Strong and sustained glycemic control by liraglutide may reduce albuminuria and improve cardiac function, reflected by BNP, LVMI, LAD, and E/e’. 24 Also, both drugs induce less hypoglycemic attacks and decreased glycemic fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Strong and sustained glycemic control by liraglutide may reduce albuminuria and improve cardiac function, reflected by BNP, LVMI, LAD, and E/e'. 24 Also, both drugs induce less hypoglycemic attacks and decreased glycemic fluctuation. 26,27 Such improved glycemic control may reduce oxidative stress and inflammation, which aside from glycemic control reduces atherosclerosis in patients taking GLP-1 RA and SGLT-2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature search, 19,096 articles were extracted, and 8 RCTs (592 patients) met the eligibility criteria for the study and were included in the meta-analysis (Fig. 1) [12][13][14][15][26][27][28]. The characteristics of the eight studies are shown in Table 1, and a network map is shown in Fig.…”
Section: Description Of Included Studiesmentioning
confidence: 99%